Analysis of Bacterial Community Associated with Aaptos sp. from Rote and Seribu Islands - EKOWATI CHASANAH; GINTUNG PATANTIS; ARIYANTI SUHITA DEWI; ENDAR MARRASKURANTO; HEDI INDRA JANUAR; STELLA STELLA; SUSAN SOKA; YOGIARA YOGIARA (Indonesian Society for microbiology, 2013)
Aaptos sp. is a marine sponge that could produce bioactive compounds such as aaptamin, aaptosin, and isoaaptamin which have activities as antitumor, antimicrobial, and antiviral. Community of bacteria associated with the sponge might correlate with production of those bioactive compounds and be affected by water environment where the sponge grow. The presence of anthropogenic stressor such as pollutans might become a burden to the waters where the biota grown and could affect the microbial biodiversity in the sponge and its active metabolite produced. The objective of this research was to analyze bacterial community associated with Aaptos sp. from Rote Island and Seribu Islands, using T-RFLP method. The results showed that bacterial community associated with Aaptos sp. from both sampling sites shared 40.81% similarity in which they were dominated by the same bacteria class of Actinobacteria, Flavobacteria, α-proteobacteria, δ-proteobacteria, and γ–proteobacteria. The bacteria collected from Rote island were more highly distributed and diverse than those from Seribu Islands. A total of 23 classes of microorganism were identified in Rote Island waters, while in Seribu Islands was 14 classes of microorganism. The presence of Actinobacteria and Proteobacteria in Aaptos sp., is allegedly involved in the production of secondary metabolites.